2009
DOI: 10.1111/j.1399-302x.2009.00538.x
|View full text |Cite
|
Sign up to set email alerts
|

Scavenger receptor A is expressed by macrophages in response to Porphyromonas gingivalis, and participates in TNF‐α expression

Abstract: Introduction-Porphyromonas gingivalis is a periodontopathic bacterium closely associated with generalized aggressive periodontal disease. Pattern recognition receptors (PRRs) participate in host response to this organism. It is likely that PRRs not previously recognized as part of the host response to P. gingivalis also participate in host response to this organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 77 publications
(97 reference statements)
1
19
0
Order By: Relevance
“…[68] reported that mice deficient in SR-A had greater levels of bone mineral density than WT mice. Our studies support that P. gingivalis stimulates SR-A ( msr 1) gene and surface protein expression and that the presence of SR-A in part limits host TNF-α production to this organism [69]. Triantafilou et al .…”
Section: Innate Sensing Of Periodontal Pathogenssupporting
confidence: 79%
“…[68] reported that mice deficient in SR-A had greater levels of bone mineral density than WT mice. Our studies support that P. gingivalis stimulates SR-A ( msr 1) gene and surface protein expression and that the presence of SR-A in part limits host TNF-α production to this organism [69]. Triantafilou et al .…”
Section: Innate Sensing Of Periodontal Pathogenssupporting
confidence: 79%
“…SRs also bind bacterial ligands and have been shown to mediate phagocytosis 29 , 35 , 36 . MARCO, SR-A and SR-B1 (CD36) can internalize oxLDL in macrophages 37 , 38 . To confirm that SRs were functional in MSCs, we examined endocytosis of lipids by using a fluorescent ligand, Dil-labeled oxidized low-density lipoprotein (Dil-oxLDL), a known endocytic marker for SRs in human macrophages 34 .…”
Section: Resultsmentioning
confidence: 99%
“…This increase is partially dependent on the major fimbriae of P. gingivalis FimA and promotes TNF-α, thus suggesting a role for SR-A in inflammation ( Fig. 2) (Baer et al 2009).…”
Section: Sp-a Increases Cell Surface Localization Of Sr-a and Potentimentioning
confidence: 94%